Identification of Novel Genes Associated with Fish Skeletal Muscle Adaptation during Fasting and Refeeding Based on a Meta-Analysis - Perez, Érika Stefani [UNESP]; Cury, Sarah Santiloni [UNESP]; Zanella, Bruna Tereza Thomazini [UNESP]; Carvalho, Robson Francisco [UNESP]; Duran, Bruno Oliveira Silva; Dal-Pai-Silva, Maeli [UNESP] (MDPI, 2022)
The regulation of the fish phenotype and muscle growth is influenced by fasting and refeeding periods, which occur in nature and are commonly applied in fish farming. However, the regulators associated with the muscle responses to these manipulations of food availability have not been fully characterized. We aimed to identify novel genes associated with fish skeletal muscle adaptation during fasting and refeeding based on a meta-analysis. Genes related to translational and proliferative machinery were investigated in pacus (Piaractus mesopotamicus) subjected to fasting (four and fifteen days) and refeeding (six hours, three and fifteen days). Our results showed that different fasting and refeeding periods modulate the expression of the genes mtor, rps27a, eef1a2, and cdkn1a. These alterations can indicate the possible protection of the muscle phenotype, in addition to adaptive responses that prioritize energy and substrate savings over cell division, a process regulated by ccnd1. Our study reveals the potential of meta-analysis for the identification of muscle growth regulators and provides new information on muscle responses to fasting and refeeding in fish that are of economic importance to aquaculture.
Keywords: fasting; fish; meta-analysis; pacu; Piaractus mesopotamicus; refeeding; skeletal muscle growth